God Made Word : An Archaeology of Mystic Discourse in Early Modern Spain - Shuger, Dale (Book collections on Project MUSE., 2022)
"This is an interdisciplinary study of mystic language across multiple genres and institutional contexts. The author combines a study of genres that have traditionally been the object of literary study--poetry, theatre, autobiography--with a language- based analysis of other areas that have largely been studied by historians or theologians. She argues that these generic separations grew out of an increasing preoccupation with the cultivation and control of interiorized spirituality beginning around 1500. She shows that by tracing certain 'mystic memes' we come to understand the emergence of different discursive rules and expectations for a wide range of representations of the ineffable. The work focuses on the circulation of mystic discourse across theological manuals, poetry, theatre, Inquisition testimony, autobiography and transatlantic encounters."--